2021
DOI: 10.1016/j.thromres.2020.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of pulmonary embolism in 1042 COVID-19 patients with respiratory symptoms: A nested case-control study

Abstract: Introduction Coronavirus disease 2019 (COVID-19) has been associated with cardiovascular complications and coagulation disorders. Previous studies reported pulmonary embolism (PE) in severe COVID-19 patients. Aim of the study was to estimate the prevalence of symptomatic PE in COVID-19 patients and to identify the clinical, radiological or biological characteristics associated with PE. Patients/methods We conducted a retrospective nested case-control study in 2 French h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
51
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 33 publications
5
51
2
1
Order By: Relevance
“…Possible mechanisms of thrombosis in found comorbidities were probably related to an endothelial injury or higher levels of inflammatory markers, common in physiopathology of these entities. Approximately two-weeks for the PE occurrence after COVID-19 onset is almost identical in all previous researches ( Espallargas et al, 2021 ; Planquette et al, 2021 ). However, in our study in three patients, PE occurred after being discharged from hospital, felt well for a short time and some of them even did not have any inflammatory consolidations visible at the time of CTPA scanning.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Possible mechanisms of thrombosis in found comorbidities were probably related to an endothelial injury or higher levels of inflammatory markers, common in physiopathology of these entities. Approximately two-weeks for the PE occurrence after COVID-19 onset is almost identical in all previous researches ( Espallargas et al, 2021 ; Planquette et al, 2021 ). However, in our study in three patients, PE occurred after being discharged from hospital, felt well for a short time and some of them even did not have any inflammatory consolidations visible at the time of CTPA scanning.…”
Section: Discussionsupporting
confidence: 86%
“…Radiologists noticed high incidence rate of the pulmonary embolism (PE), even despite thromboprophylaxis given. So far, there are several published case reports ( Brüggemann et al, 2020 ; Cellina & Oliva, 2020 ; Jafari et al, 2020 ) and researches ( Espallargas et al, 2021 ; Grillet, 2020 ; Karolyi et al, 2021 ; Leonard-Lorant et al, 2020 ; Lodigiani et al, 2020 ; Planquette et al, 2021 ) addressing the PE in a setting of COVID-19 infection. Literature showed the thrombotic complications occurred most often in seriously ill individuals ( Middeldorp et al, 2020 ) even without risk factors and in some cases even despite the given thromboprophylaxis.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by six studies which reported a significant association between severity of lung parenchymal abnormalities at CT and PE [ 32 , 40 , 44 , 45 , 71 , 74 ]. However, such an association was not demonstrated in 13 other studies [ 24 , 30 , 31 , 37 , 42 , 43 , 49 , 50 , 52 , 60 , 62 , 78 ]. Therefore, there are probably other COVID-19- and host-related factors that are associated with the occurrence of PE.…”
Section: Discussionmentioning
confidence: 82%
“…However, there is no uniformly accepted D-dimer threshold to discriminate COVID-19 patients with and without PE. Twelve studies used different D-dimer cutoff levels (varying between 1000 and 4800 μg/L), yielding sensitivity and specificity values which varied between 63–100% and 23–84%, respectively [ 11 , 24 , 33 , 52 , 58 , 60 , 71 , 74 , 78 , 82 , 86 , 89 ]. These D-dimer cutoff levels were at least twice as high compared to the conventional D-dimer cutoff level of 500 μg/L, which is usually employed in the general population as a screening test for venous thromboembolism [ 104 , 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the initial reports on the incidence and prevalence of thrombotic complications were relatively small and retrospective, several larger and/or prospective studies further confirmed and extended the initial observations. [ [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] ] These studies showed the relevance of considering concomitant pulmonary embolism (PE) in patients with respiratory decline [ 9 ], the results of screening for deep vein thrombosis in acutely ill patients on normal wards [ 12 ] and critically ill patients in intensive care units [ 22 ], the impact of COVID-19 on the prevalence of catheter related thrombosis [ 6 ], differences in the incidence of thrombotic complications between the first and second wave in Europe [ 28 ] and the incidence of thrombotic complications after hospital discharge. [ 27 ] Moreover, several studies confirmed the observation made by initial publications on thrombotic complications in COVID-19 patients that a diagnosis of thromboembolism per se was associated with a more complicated in-hospital clinical course, higher incidence of admittance to the intensive care unit and higher all-cause mortality.…”
mentioning
confidence: 99%